Should We Resect Hoffa's Fat Pad during Total Knee Replacement? - Sellars, Hannah; Yewlett, Alun; Trickett, Ryan; Forster, Mark; Ghandour, Adel (The Journal of Knee Surgery, 2017)
Resection of Hoffa's fat pad during total knee arthroplasty is sometimes performed to improve access and view. Opponents of this technique argue that sacrificing the fat pad potentially compromises blood supply to the patellar tendon and it can subsequently shorten. Our objective was to identify any difference in the Insall-Salvati ratio of knees undergoing total knee arthroplasty between a cohort that had Hoffa's fat pad preserved and the one that had Hoffa's fat pad completely excised. The total knee arthroplasties by two surgeons at our institution were reviewed over a 3-year period. Surgeon A routinely preserves the fat pad and surgeon B routinely excises the fat pad. Radiographs preoperatively, immediately postoperatively, and at a minimum of 1-year follow up were analyzed for the Insall-Salvati ratio. A total of 161 knees were reviewed, 65 in the preserved group and 96 in the excised group with a mean age of 67 and 70 years, respectively. The mean preoperative Insall-Salvati ratio for the preserved group was 1.12 (±0.145) and excised group 1.16 (±0.168) (p = 0.094). The mean immediate postoperative Insall-Salvati ratio for the preserved group was 1.10 (±0.154) and for excised group 1.18 (±0.194). The difference in Insall-Salvati ratio from preoperative to the immediate postoperative period in the preserved group compared with the excised group demonstrated a significant difference (p = 0.010). However, the change of Insall-Salvati ratio at 1 year did not significantly differ between the groups (p = 0.059). There does not appear to be any difference in the Insall-Salvati ratios of both groups at 1 year's follow up; therefore, this study radiologically at least supports the use of either technique.
Keywords: Hoffa's fat pad; Insall-Salvati ratio; total knee arthroplasty; infrapatellar fat pad